Effectiveness of Pre-operative Tranexamic Acid Administration Against the Amount of Bleeding During and After Open Reduction Internal Fixation (ORIF) in Closed Femur Fractures - Hengky Irianto; Primadika Rubiyansah (Sriwijaya Journal of Surgery, 2019)
ABSTRACT Introduction. In femoral fractures case, bleeding often occurs and is accompanied by injury to other organs, so the possibility of impaired circulation (shock hemorrhagic) will be greater, especially at productive age. This study was aimed to evaluate the benefits of giving pre-operative tranexamic acid to sufferers of femur fractures accompanied by circulatory disorders and without circulation disorders in reducing peri-operative and postoperative bleeding ORIF. Method. This study was a clinical experimental test with a cohort design at the Central Surgical Installation of Dr. Mohammad Hoessin Hospital Palembang. Samples were taken from patients who underwent ORIF Femur surgery, with a type of Hansen Winquist fracture type 0-2, which was pierced with tranexamic acid 10 mg / Kg BW. Result. Intraoperative hemorrhage in ORIF in both treatment groups where patients with a history of preoperative shock had more amount of bleeding than the group who had no history of preoperative shock. Whereas from the amount of post-operative drainage, there were no significant differences in the two treatment groups. Conclusion. The group of patients with a history of hemodynamic disorders (shock) given intravenous tranexamic acid, is useful in reducing intraoperative bleeding, but not significant to reduce postoperative bleeding in both treatment groups